COMPARATIVE STUDY OF LENTIL EXTRACT AND GRAFTED LENTIL EXTRACT AS COAGULANTS IN WATER AND WASTEWATER TREATMENT - SIONG , CHUA CHIN (2019)
Increasing awareness on the detrimental effects of inorganic chemical coagulants and sustainable treatment has paved the way to develop environmentally-benign natural coagulants for water and wastewater treatment. In this research, brown, green, and red lentil extracts (LE) have been evaluated as a natural coagulant for the turbidity reduction. The physicochemical properties of LE were evaluated through field emission scanning electron microscopy (FESEM), Fourier-transform infrared spectroscopy (FTIR), zeta potential analysis, and energy-dispersive X-ray (EDX) analysis. Red LE was found to be an anionic polymer with hydroxyl and carboxyl functional groups. The red LE as coagulant was outperformed conventional chemical coagulant, aluminium sulphate (alum) in acidic wastewater treatment, which achieved up to 98.87% turbidity removal with an optimum concentration of 26.3 mg/L in 3 min. To enhance the efficiency of the LE, 2-methacryloyloxyethyl trimethyl ammonium chloride (DMC) was introduced into the backbone of LE polymer through microwave induced grafting method to synthesize a novel plant-based coagulant, LE-g-DMC.